UNDERSTANDING SOLE PROPRIETORSHIP UNDER THE JOB CREATION LAW: A LEGAL HERMENEUTICS PERSPECTIVE - Yusuf, Muhammad Arham (Faculty of Law, Universitas Lampung, 2024)
The issue of tender offers has gained prominence due to several high-profile cases involving the takeover of public companies, which have led to significant losses for shareholders, particularly public shareholders. The regulatory framework governing takeovers and tender offers is primarily established by Law No. 8 of 1995 concerning the Capital Market and Government Regulation No. 27 of 1998. The enactment of Law No. 21 of 2011 concerning the Financial Services Authority (OJK) in 2011 marked a significant shift in regulatory oversight, transferring authority over macroeconomic matters, including takeovers and tender offers, from Bank Indonesia to OJK. A notable example is the 2020 takeover of PT Garudafood Putra Putri Jaya Tbk. of PT Mulia Boga Raya Tbk. This study seeks to analyze the regulatory arrangements for tender offers in Indonesia and evaluate the impact of such takeovers on the public companies involved. The research employs normative legal research methodologies with a statutory approach, utilizing both primary and secondary legal materials.